Does satisfaction affect the outcomes of counseling services for college students? - Purnama, Diana Septi; Sutanti, Natri; Kurniasari, Mitta; Lestari, Rizqi; Omar, Mariani Binti (Psikopedagogia, 2025)
This research aims to determine the effect of college students' or counselees' satisfaction on the outcomes of counseling services at one of the universities in Yogyakarta. The type of research is cross-sectional, with 119 counselees as the research samples. The sampling technique used was total sampling. The data collection technique was carried out by giving two questionnaires to counselees using counseling services after they completed their counseling. Questionnaire 1 contains questions regarding satisfaction with counseling services, while Questionnaire 2 contains perceived counseling results. Descriptive analysis and Spearman correlation test were carried out in this study. The results showed that 74% of clients stated they were satisfied with the services they received, and 78.2% said they would recommend the services to others. The results of the correlation test produced a coefficient of 0.588 (p<0.005), which shows a significant relationship between the client's satisfaction and the counseling outcome. Counselees feel satisfied and gain new insight from the counseling services. Counselees also found their strength, felt more hopeful, and overcame their problems after attending counseling services. The level of client satisfaction is not just a subjective statement of satisfaction but is accompanied by a real impact or result of counseling. Therefore, counseling services in higher education need to be provided, which has led to significant changes for the counselees.